Parameter determination of 0.5 hp induction motor based on load factor test - A case study - Ismail, Daut, Prof. Dr.; Gomesh Nair, Shasidharan; Muhammad Irwanto; Yanawati, Y.; Nor Shafiqin, S.; Mohd Irwan, Yusoff (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/